Monitoring and Enhancing Education Quality Through Digital Technologies - Sodiqov Rafikjon Turobjon o'g'li (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2026)
The rapid advancement of digital technologies has significantly transformed the education sector, providing innovative tools for monitoring and improving educational quality. This article explores the role of digital technologies in assessing, controlling, and enhancing the quality of education. It analyzes modern digital platforms, data-driven decision-making systems, and artificial intelligence tools used in education management. The study highlights how digital systems enable real-time monitoring, personalized learning, and improved transparency. Additionally, it discusses challenges such as data security, digital inequality, and teacher readiness. The findings suggest that integrating digital technologies into educational systems can lead to sustainable improvements in teaching effectiveness and student outcomes.